Determinants of GCC Women Entrepreneurs Performance: Are they Different from Men? - Madbouly, Araby; Khayyal, Huda Al; Mourssi, Anwar; Wakeel, Waleed Al (Journal of Asian Business Strategy, 2021)
The study aims to understand the impact of different factors on the performance of GCC entrepreneurs and to what extent this effect is different between women and men. To accomplish the determined aim, the research used quantitative research method. Survey strategy has been implanted to collect the data via structured questionnaire technique. The questionnaire was distributed online for 750 GCC male and female entrepreneurs. 262 responses have been received. The data was analysed using descriptive analysis while ANOVA was implemented to assess the differences between men and women in their reflections towards determinants of their performance. The investigation found that females consider education, training and business networks and access to finance are significant factors impact their performance. GCC women’s performance is affected by these determinants more than men counterparts. Both men and women entrepreneurs believe that access to finance as an important determinant for their performance without significant difference between the two genders. This research provides a proper guidance for the policy makers to give more attention to education and training for women entrepreneurs. More focus on entrepreneurship education may foster the women entrepreneurship. Training is also a significant determinant of their performance than men. This may pay the attention to the role of supporting institutions, even formal or informal; to design proper training programmes for women entrepreneurs. Supporting institutions needs also to play more roles towards enforcing the networks for women entrepreneurs.